'Closing the gap': the conditions under which children in care are most likely to catch up in mainstream schools. (4th March 2022) - Sinclair, Ian; Fletcher, John; O'Higgins, Aoife; Luke, Nikki; Thomas, Sally
BSTRACT: Children 'in care' have, on average, lower educational attainment than their peers. This article tests the hypothesis that many of these children can 'catch-up', if in stable placements and secondary schools 'apparently effective' with other children with 'similar' difficulties. In a cohort of 542, 998 16-year-old English children in mainstream schools, those in care for at least a year were on average 148, 465 ranks behind their peers on measured attainment at age 7. At age 16, 21% of this group had 'caught up' improving their ranking by at least this amount. Allowing for covariates, we found that schools were differentially effective for disadvantaged pupil groups defined by eligibility for free school meals at age 7, in the bottom 3 deciles of attainment at entry to secondary school, or deemed 'in need' or as having behavioural, emotional or social difficulties. As predicted, the conditions for children in care catching up related to placement stability and measures of their school's apparent impact on these disadvantaged groups. In the 'worst' conditions 4% caught up as against 52% in the 'best'. The results support the hypotheses that best practice can reduce the educational gaps between children in care, other low attaining groups and their peers.